2015
DOI: 10.1002/2015gl063325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil moisture on dust outbreaks in East Asia: Using satellite and assimilation data

Abstract: This study is the first assessment of the effects of soil moisture on dust outbreaks using satellite‐derived aerosol optical depth (AOD) and global assimilation data on the sand regions across East Asia. The relationships among dust outbreaks, soil moisture, and wind speed were estimated using data sets of the Moderate Resolution Imaging Spectroradiometer and Global Land Data Assimilation System collected over 11 years (2003–2013). The mean AOD exponentially decreased with increasing soil moisture under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 42 publications
1
40
0
2
Order By: Relevance
“…In addition, vegetation‐atmosphere interactions and dust‐climate feedbacks are also important processes in local atmosphere‐land interactions, despite their impacts on each other. Decreased soil moisture can markedly enhance dust outbreaks under certain wind conditions [ Kim and Choi , ]. The ability of atmospheric dust to suppress precipitation can contribute to a positive desertification feedback whereby plant mortality and enhanced dust emissions result from the reduced vegetation cover [ Rosenfeld et al ., ; Huang et al ., ].…”
Section: Impacts Of Atmosphere‐land Interactionsmentioning
confidence: 99%
“…In addition, vegetation‐atmosphere interactions and dust‐climate feedbacks are also important processes in local atmosphere‐land interactions, despite their impacts on each other. Decreased soil moisture can markedly enhance dust outbreaks under certain wind conditions [ Kim and Choi , ]. The ability of atmospheric dust to suppress precipitation can contribute to a positive desertification feedback whereby plant mortality and enhanced dust emissions result from the reduced vegetation cover [ Rosenfeld et al ., ; Huang et al ., ].…”
Section: Impacts Of Atmosphere‐land Interactionsmentioning
confidence: 99%
“…In such cases, higher wind speeds are required to uplift dust particles. Overall, similar conclusions have been obtained by Kim and Choi [] who have compared the MODIS Deep Blue AOD (column atmospheric) to the wind speed and soil moisture from Global Land Data Assimilation System (GLDAS/NOAH). However, the transported aerosols, which are not affected by the soil moisture and wind speed, from the surrounding areas could significantly impact the results.…”
Section: Resultsmentioning
confidence: 99%
“…When no soil moisture data is available for some pixels during a month, the pixel is considered to be a plausible dust emitting surface regarding the soil moisture criterion. Kim and Choi (2015) have studied the correlation between measured dust AOD, wind speed and soil moisture. They have 10 shown that "the threshold soil moisture for dust outbreak increased with increasing wind speed", and that for a volumetric soil moisture higher than 16% the measured AODs are only barely affected by wind speed conditions, indicating that this value could be a general soil moisture threshold above which dust emissions are almost impossible.…”
Section: Soil Moisturementioning
confidence: 99%